Fiction or non-fiction: Parent-reported book preferences of their preschoolers with autism spectrum disorder. (December 2019) - Armstrong, Rebecca M; Paynter, Jessica; Westerveld, Marleen F
Background and aims: Children's early interactions with books are important for fostering development of oral language and emergent literacy skills. It is not known whether children diagnosed with autism spectrum disorder show different preferences for text types in the home environment prior to school entry. The current study aimed to: (i) investigate parent-reports of the favourite books of their children with autism spectrum disorder compared to typically developing children and (ii) identify whether there are differences in the reasons why books were preferred across the two groups. Methods: Participants included children (aged 26–70 months) with autism spectrum disorder ( n = 41) and typically developing peers ( n = 164). Parent-reports of their child's current favourite book/s were coded as fiction versus non-fiction and also category type. Parents also reported why the book was considered a favourite and this was coded. Results: There were no differences between groups for fiction versus non-fiction, with both groups preferring fiction (>95% of responses). A strong category preference for animal topics across both groups was present. Significant group differences were found when asked to select specific reasons for favourite book preferences. Conclusions: This study provides preliminary evidence of similarities between preschool children with autism spectrum disorder and typically developing peers' preferences for fiction books during the early years. Implications: It should not be assumed that children with autism spectrum disorder have different preferences for book types compared to typically developing children in the early years of development. Providing preschoolers with a range of book types during the preschool years will help to facilitate early language and emergent literacy skills.